Layoffs, Wages and Unemployment Insurance - BURDETT, Kenneth (Institutional Knowledge at Singapore Management University, 1983)
The influence of unemployment insurance on wage and layoff behavior is analyzed in the context of optimal labor contracts. Responses of contract terms to changes in economic parameters are shown to depend in general on the nature of the initial contract, the degree of workers' risk aversion, and the resolution of bargaining conflict. Layoffs are not necessarily reduced by an increase in experience rating or a reduction in the UI benefit. Product demand fluctuations tend to induce procyclical employment fluctuations but not wage fluctuation. An implication of optimal contracts with private insurance suggests a reason for government intervention in UI provision. © 1983.